Maternal gut microbiota in pregnancy dictates offspring metabolic phenotype - Kimura, Ikuo; Miyamoto, Junki; Ohue-Kitano, Ryuji; Watanabe, Keita; Yamada, Takahiro; Onuki, Masayoshi; Aoki, Ryo; Isobe, Yosuke; Kashihara, Daiji; Inoue, Daisuke; Inaba, Akihiko; Takamura, Yuta; et al. (Dryad, 2019)
Antibiotics and dietary habits can affect the gut microbial community,
influencing disease susceptibility. Although the influence of microbiota
on the postnatal environment has been well documented, much less is known
regarding the impact of gut microbiota at the embryonic stage. Here, we
show that maternal microbiota shapes the metabolic system of offspring.
During pregnancy, short-chain fatty acids produced by the maternal
microbiota dictate the differentiation of neural, intestinal, and
pancreatic cells through embryonic GPR41 and GPR43. This developmental
process helps maintain postnatal energy homeostasis, as evidenced by the
fact that offspring from germ-free mothers are highly susceptible to
metabolic syndrome, even when grown under conventional conditions. Thus,
our findings uncovered a missing link between the maternal gut environment
and the developmental origin of metabolic syndrome.